Iceland : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper for Iceland reports that it faces a considerably less favorable inflation-output variability trade-off than do Canada or the United States. A number of measures should be considered that could help minimize the cost of inflation breaching the tolerance band and help to lower the probability of such events occurring. To effectively target inflation, central banks need to be forward looking, responding early to prospective demand pressures. Having housing prices explicitly in the target ensures that the central bank will monitor developments in the housing market closely.